Stimulating the Division of Innovative Labor by Regional Competition for R&D Subsidies – A New Approach in German Innovation Policy - Alexander Eickelpasch; Michael Fritsch (European Regional Science Association (ERSA), 2004)
The paper deals with a new approach in German innovation policy that organizes contests of initiatives for public funds. Based on an overview of the different programs we investigate the advantages and problems of such an approach. We find that this type of policy may have a large impact and can, therefore, be regarded a rather efficient instrument of innovation policy. Compared to conventional policies implementation is a much more critical issue. The contest approach may require more flexibility on the side of the administration, particularly with regard to the design of the assistance. The main disadvantage is the additional time that is required for conducting the contest. As a distinct “picking the winner” instrument it is not suited as a means for achieving a leveling-out of welfare levels. Keywords: Innovation policy, regional competition, innovation networks JEL-classification: H32, O18, O38, R11
Keywords: H32; O18; O38; R11; 330; Innovation policy; regional competition; innovation networks